Bicarbonate supplementation via lactate efflux improves anaerobic and cognitive performance in elite combat sport athletes - Chycki, Jakub; Zając, Adam; Toborek, Michał (Biology of Sport, 2021)
The aim of this study was the assessment of sodium bicarbonate supplementation (NaHCO3-) on anaerobic and cognitive performance, assuming ergogenic effect of HCO3 by improving buffering capacity and greater lactate efflux, which may have indirect effect on circulating neurotrophin level (e.g BDNF, IGF-1) and memory. Sixteen well-trained judo athletes completed a randomized trial of either a NaHCO3 - (EG) (5000 mg x 2/day/90 min before training) or placebo for 21 days (CG). Before and after treatment, athletes completed double Wingate test (Wt) protocol following which they performed perceived Working Memory test (pWM). Results suggested significant increase in Upper Limb Total Work (with p = 0.011), Mean Power (with p = 0.001), post exercise LA concentration (from 15.51 mmol/L to 18.10 mmol/L with p = 0.01) and HCO3rest concentrations (from 27.37 mmol/l to 28.91 mmol/l with p = 0.001), when compared to baseline values in EG. The analysis showed statistically significant increase in values for IGF-1 (with p = 0.001) and decrease for cortisol and BDNF (with p = 0.001) in EG and CG, when pre and post exercise values were compared. We also revealed statistically significant decrease in values for display time after ingestion of HCO3 between pre and post exercise (with p = 0.002) In conclusion, the lack of a substantial relationship between exerkines (IGF-1, BDNF) and memory in the present study might suggest that exercise induced lactate levels is dominant mechanism improving working memory in well-train athletes.